2020
DOI: 10.3390/en13236265
|View full text |Cite
|
Sign up to set email alerts
|

The Financial Development-Renewable Energy Consumption Nexus in the Case of Azerbaijan

Abstract: This article analyzed the relationship between financial development, renewable energy consumption, economic growth, and energy prices in Azerbaijan by employing time series data for the time span of 1993–2015. The autoregressive distributed lagged (ARDL) technique was applied in empirical estimations, because it performs better than all the alternative techniques in small samples, which was the case here in this article. The results of estimation found that there is a positive and statistically significant in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(17 citation statements)
references
References 36 publications
(43 reference statements)
3
12
0
2
Order By: Relevance
“…The impact of financial development on REC, study documents positive association in Brazil (a coefficient of 0.134), in Russia (a coefficient of 0.049), and in India (a coefficient of 0.071) and in China (a coefficient of 0.049), indicating the financial expansion enhances the green energy consumption through investing in the energy sector, especially for the production of renewable energy. Study findings are in line with Eren, Taspinar, and Gokmenoglu [78], Naqvi, et al [110], Mukhtarov, Humbatova, Hajiyev, and Aliyev [79]. More specifically, a 10% growth in financial development can result in Brazil's renewable energy consumption by 1.34%, in Russia by 0.49%, in India by 0.71%, and in China by 0.49%, respectively.…”
Section: Model Estimation and Interpretationsupporting
confidence: 86%
See 2 more Smart Citations
“…The impact of financial development on REC, study documents positive association in Brazil (a coefficient of 0.134), in Russia (a coefficient of 0.049), and in India (a coefficient of 0.071) and in China (a coefficient of 0.049), indicating the financial expansion enhances the green energy consumption through investing in the energy sector, especially for the production of renewable energy. Study findings are in line with Eren, Taspinar, and Gokmenoglu [78], Naqvi, et al [110], Mukhtarov, Humbatova, Hajiyev, and Aliyev [79]. More specifically, a 10% growth in financial development can result in Brazil's renewable energy consumption by 1.34%, in Russia by 0.49%, in India by 0.71%, and in China by 0.49%, respectively.…”
Section: Model Estimation and Interpretationsupporting
confidence: 86%
“…It refers to financial development proxies' respective elasticities on renewable energy consumption, all the proxies except stock market development have exposed statistically insignificant linkage with renewable energy consumption in EU nations. Mukhtarov, et al [79] gauged the effects of financial sector development on renewable energy consumption in Azerbaijan from 1993 to 2015 by implementing autoregressive distributed lagged (ARDL) tests. The study findings reveal positive statistically significant effects running from financial sector development and economic growth to renewable energy consumption in the long-run.…”
Section: Financial Development and Renewable Energy Consumptionmentioning
confidence: 99%
See 1 more Smart Citation
“…These outcomes of FD have good effects on cost of clean energy and respectably highlights the importance of FD in consumption of renewable energy (Anton and Nucu 2020 ). Financial sector developments enhance usage of renewable energy (Khan et al 2020 ; Mukhtarov et al 2020 ; Qamruzzaman and Jianguo 2020 ). According to Pata ( 2018 ), FD positively affects economic and economic growth may increase environmental pollution.…”
Section: Relevant Literaturementioning
confidence: 99%
“…The belief that higher GDP is correlated with greater use of renewable energy is based on the assumption that higher income means more resources available to implement and promote costly sustainable environmental alternatives, including greater deployment of renewables [56]. The correctness of the view about the positive impact of GDP on renewable energy consumption (supply) was confirmed by many scholars who researched GDP per capita [57][58][59][60][61][62][63][64] or GDP in absolute terms [65]. In addition, Przychodzen and Przychodzen [66], using data from 27 transition countries over the years 1990-2014 have found that higher GDP growth stimulate renewable energy generation.…”
Section: Control Variablesmentioning
confidence: 99%